Effects of Extrusion on the Available Energy and Nutrient Digestibility of Wheat and Its Application in Weaned Piglets - Ge Zhang; Xing He; Zhiqiang Sun; Tenghao Wang; Ling Liu; Jinbiao Zhao; Zeyu Zhang (Animals)
Experiments were designed to investigate the effect of extrusion on the available energy and nutrient digestibility of wheat, and to further evaluate the effects of incorporating extruded wheat into the diet on growth performance, diarrhea rates, health status, and fecal microbiota of weaned piglets. In Exp. 1, twelve crossbred barrows, with an initial body weight (BW) of 12.0 ± 0.73 kg, were randomly assigned to two treatment groups (wheat and extruded wheat) to determine the digestible energy (DE) and metabolizable energy (ME). Additionally, nine crossbred barrows (initial BW, 13.73 ± 0.59 kg) fitted with ileal cannulas, were arranged in a 9 × 2 Youden square design, including three diets (N-free diet, wheat, and extruded wheat), aiming to measure the standard ileal digestibility of amino acids (AAs). In Exp. 2, 96 pigs (initial BW, 8.58 ± 0.52 kg) were randomly divided into two treatments (CON and 35% extruded wheat) based on BW, with each treatment having six pens, each pen containing four boars and four sows. The results indicated that extrusion significantly increased the DE and ME of wheat and the standard ileal digestibility of most AAs (p < 0.05). Incorporating 35% extruded wheat did not affect the growth performance, diarrhea rates, nutrient digestibility, or health status of the weaned piglets (p > 0.05). However, it tended to enhance the α-diversity of fecal microbiota (p = 0.07) and increased the relative abundance of beneficial bacteria (p < 0.05). In conclusion, extrusion increased the feeding value of wheat, and the inclusion of 35% extruded wheat in the diet increased the relative abundance of beneficial microbes in feces.